Urgensi Kedudukan Lembaga Badan Permusyawaratan Desa Menurut Peraturan Perundang-Undangan - Bustamin; Intan Putri Azhari; Adriyanti Agustina Putri; Evi Marlina; Rama Gita Suci; Siti Rodiah; Zul Azmi; R Septian Armel; Rizda Akira Henur; Nadila Rahayu (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Village Advice Center is a village institution that has very strategic roles and functions as well as tasks in the management of the village administration in accordance with the mandate of Law No. 6 of 2014 on Villages. The passing of the law has an impact on the paradigm shift of the BPD institution from an element of the village administration organizer to an institution outside the village administration. The problem that has arisen so far is the poor mastery/understanding of the BPD members with regard to the laws and regulations relating to BPD, which are actually a guide in the performance of their functions and duties. This service is conducted to improve the human resources of the BPD Pulau Permai Village in understanding and applying the BPD legislation. This activity was conducted in the Pulau Permai Village Meeting Building in Kec. Mining district. Kampar. Training and professional advice are chosen as an approach, in particular by explaining the material in tutorials and discussions as well as by providing legal provisions and BPD guidelines.